The Effectiveness of Kombucha Coffee (Coffea canephora) Extract Antioxidant Moisturizer on UV-B Induced Skin Epidermal Thickness - Lifia Chandra; Renata Prameswari; Prima Arundani; Henry Purbowo Sintoro (Berkala Ilmu Kesehatan Kulit dan Kelamin (Periodical of Dermatology and Venerology))
Background: The exposure to UV-B (280-320 nm) in Indonesia's tropical sunlight leads to the accumulation of free radicals, which in turn causes the formation of dry skin and thickening of the epidermis, a sign of skin photoaging. Topical intervention with moisturizers containing antioxidants is one approach to prevent further damage. The addition of kombucha coffee extract from fermented robusta coffee (Coffea canephora) with SCOBY (symbiotic cultures of bacteria and yeasts) can be a source of antioxidants. Purpose: To evaluate the effect of Coffea canephora extract as an antioxidant moisturizer in reducing epidermal thickness on mice’s back skin exposed to UV-B irradiation. Methods: This research is a true experimental design with a post-test only control design. The sample used in this research is thirty male white mice (Rattus norvegicus), which were divided into six groups and were UV-B irradiated for two weeks with total dosage of 980 mJ/cm2.At the end of the treatment, skin samples were excised and stained histologically with Mollory Azan (MA) to evaluate the thickness of the epidermis. Data obtained were analyzed statically with SPSS. Result: The Kruskal-Wallis test demonstrated significant results (0.0001, p<0.05) across all groups, indicating the efficacy of the kombucha coffee extract antioxidant moisturizer in reducing epidermal thickness. Conclusion: The application of Coffea canephora extract antioxidant moisturizer provided photoprotection against UV-B induced hyperplasia skin epidermis with the concentration of 5% and 10% extract.